Case report: Severe non-pigmenting fixed drug eruption showing general symptoms caused by chondroitin sulfate sodium - Otsuka, Haruhiko; Fukumoto, Takeshi; Oka, Masahiro; Nishigori, Chikako (Frontiers in Medicine, 2022)
Non-pigmenting fixed drug eruption (NPFDE) is a subtype of fixed drug eruption (FDE) in which repeated eruptions occur at the same site. Clinically, NPFDE disappears without pigmentation changes; however, it sometimes causes fever or arthralgia. Its histopathological characteristics reportedly include infiltrations of CD8-positive T cells with a paucity of melanocytes as compared to FDE. We present the first case of severe NPFDE exhibiting general symptoms caused by chondroitin sulfate sodium. The patient was a 44-year-old man. Intravenous injection of chondroitin sulfate sodium caused erythema in the affected area. A histopathological examination of the biopsy tissue revealed infiltration of CD3-positive lymphocytes (both CD4-positive and CD8-positive lymphocytes) into the epidermis, minimal liquefaction degeneration in the basal layer of the epidermis, and few dermal melanophages, which may be responsible for non-pigmentation.